Subverting Racialized Mobility Regimes: Ethical Research with Migrant Youth in an Age of Securitization - Roozbeh Shirazi (Social Sciences)
In France, minoritized migrant youth—a term encompassing various legal statuses and migration trajectories—are subject to systems of surveillance that include racialized policing, school securitization policies, and programs to counter extremism. These institutional practices are complemented by hostility within everyday public spaces and broader systems of representation. Together, institutional and everyday forms of surveillance constitute racialized mobility regimes for migrant youth within and beyond educational spaces. For researchers who work with migrant youth, such landscapes pose ethical demands—what forms of critical awareness, anticipatory planning, and improvisatory practices are necessary to mitigate harms resulting from participation in their projects? Drawing upon an autoethnographic revisiting of a 16-month digital storytelling engagement with newcomer migrant and refugee youth in two French high schools, I discuss the creation of a “youth researcher” pass in anticipation of the racialized surveillance confronting migrant youth in France. Informed by the works of Walter Benjamin and Michel de Certeau on mobility, storytelling, and facsimiles, as well as political developments in France, I argue that in settings in which migrant presence is deemed a threat, researchers must unapologetically opt for an ethical stance that takes protection of participants’ humanity—rather than legality—as its core aim.